Kia aiō ngā ngaru, kia hora te marino: smoothing the waters in natural resource management to mitigate risk and uncertainty. (June 2023) - Hyslop, Jade; Harcourt, Nikki; Awatere, Shaun; Hikuroa, Dan; Blackett, Paula; Heron, Richard Le
Aotearoa (New Zealand) is undertaking reforms in natural resource management, and there are promising signals that Indigenous perspectives will be included alongside science for decision-making. Any resource management system is underpinned by worldviews, from which values stem and then risk and uncertainty derive. Māori (the Indigenous peoples of New Zealand) and Eurocentric notions of risk and uncertainty are fundamentally different because knowledge holders have different worldviews. Eurocentric concepts of risk and uncertainty continue to frame policy, making it challenging for Māori knowledge to shape policy that is relevant for decision-making in Aotearoa. We explore Māori perspectives of risk and uncertainty and literature, identifying common attributes across natural resource management frameworks, and identify issues of risk and uncertainty from the perspective of Māori experts. We conclude that a Māori approach to enhancing natural resources is more aligned to current environmental policy compared with standard approaches for risk assessment and reducing uncertainty.